Identification of Bipolaris bicolor and Bipolaris sorokiniana on wheat seeds (Triticum aestivum L.) in Brazil - Morejon,Kendra R. (2006)
Diseases caused in wheat by Helminthosporium spp. have led to considerable yield and production losses. Different species in this genus are associated with wheat seeds. In Brazil, spot blotch in wheat is caused by Bipolaris sorokiniana (Sacc) Schoem, and another fungus Bipolaris bicolor (Mitra) Shoem that has been also isolated from wheat seeds. The current study was undertaken to identify the most frequent fungus species that normaly infects wheat seeds and compared them with B. sorokiniana. The fungus Bipolaris bicolor (Mitra) Shoem., isolated from wheat seeds cultivar IAPAR, was identified by taxonomic methods and compared with the fungus Bipolaris sorokiniana (Sacc.) Shoem., in relation to growth characteristics on the seeds, as well as to growth characteristics in PDA and morphology of the structures. Type of colony observed on the seeds is important for the differentiation between the fungus species. Bipolaris sorokiniana presented black colonies, which were well-adherent to the seeds, whereas B. bicolor presented grayish, aerial, cotton-like colonies. The size of the conidia also differed in length and width, and B. bicolor presented the smallest dimensions. In relation to septa, B. bicolor conidia presented deep ones, with dark color bases, but seldom presented dark apex. Bipolaris sorokiniana presented homogenous color.